ECONOMIC MECHANISMS FOR THE RECOVERY AND ENHANCEMENT OF COMPETITIVENESS IN POST-CONFLICT REGIONS - SHANDOVA, Nataliia; HENS, Oleksii; HODUNOV, Serhii (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines the economic mechanisms for the recovery and enhancement of the competitiveness of post-conflict regions in the context of digital transformation and global instability. It substantiates that effective regional recovery cannot be limited to isolated physical reconstruction measures but requires the formation of a comprehensive, interconnected system of economic policy instruments. Such a system must integrate investment, financial, institutional, and digital tools that mutually reinforce each other and create conditions for sustainable development. The analysis of key constraints on post-conflict development reveals that regions face infrastructure destruction, reduced investment attractiveness, degradation of human capital, administrative incoherence, limited access to financing, and disrupted market linkages, all of which exacerbate socio-economic vulnerability and increase the risk of recurrent crises. A conceptual model of economic recovery mechanisms is proposed, consisting of four interrelated components. The investment component envisages the creation of special economic recovery zones and the use of public-private partnerships to modernize infrastructure. The financial component includes guarantee funds, municipal bonds, and co-financing programs with international institutions to expand access to capital. The institutional component focuses on establishing recovery agencies, developing multilevel coordination mechanisms, and implementing scenario-based planning that accounts for security risks. The digital component ensures the integration of e-governance, investment monitoring platforms, and online business services to increase transparency, reduce transaction costs, and stimulate innovation. Implementation of this model provides a foundation for structural modernization, increases the resilience of regional economies to external shocks, and creates the prerequisites for their integration into the national economic space. The prospects for further research include practical testing of the model in specific regions, its adaptation to different recovery scenarios, and the assessment of its socio-economic impact.